Titanium alloy plate and glasses
By optimizing the metallographic structure of the titanium alloy plate, improving the area ratio and average grain diameter of the α phase, and controlling the grain orientation, the shortcomings of the titanium alloy in terms of processability and mirror properties are solved, and excellent bending and high gloss are achieved.
Patent Information
- Application Number
- CN202380061884.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-06-12
- Publication Date
- 2025-04-04
AI Technical Summary
Existing titanium alloys have difficulty meeting the higher requirements in recent years in terms of processability and mirror properties, especially in terms of bending and smoothness of the polished surface.
By optimizing the metallographic structure of the titanium alloy plate, the area ratio and average grain diameter of the α phase are improved, and the area ratios of αt-30 and αc-30, as well as the average value of GOS are controlled to ensure the uniformity of grain orientation and the reduction of deviations.
The excellent processability and mirror properties of the titanium alloy plate are achieved, and good bending and high gloss after polishing can be maintained in the shape of the product with high precision.
Smart Images

Figure BDA0005284769630000181 
Figure BDA0005284769630000191 
Figure BDA0005284769630000201
Abstract
Description
Technical Field
[0001] The invention relates to a titanium alloy plate and glasses.
[0002] This application claims priority based on Japanese Patent Application No. 2022-136623 filed in Japan on August 30, 2022, and the contents are incorporated herein by reference. Background Art
[0003] Titanium alloys are used in accessories such as glasses and watch cases due to their light weight, high corrosion resistance, and biocompatibility. Stainless steel is also used for similar purposes, but titanium has a smaller specific gravity than stainless steel, which is beneficial for lightweighting. In addition, titanium is also excellent in that there is no worry about causing metal allergies. On the other hand, titanium has a problem that its mirror finish after polishing is not as good as stainless steel.
[0004] For example, pure titanium has a low hardness and large indentations caused by abrasive particles, so it is sometimes difficult to obtain a mirror surface after polishing. On the other hand, conventional titanium alloys with improved hardness are sometimes difficult to process into the high-precision product shapes of recent years. In addition, in titanium alloys, the state of the metallographic structure on the surface after polishing sometimes leads to the appearance of crystal grains or unevenness, and it is difficult to obtain excellent mirror surface properties by simply increasing the hardness.
[0005] Therefore, a titanium alloy having excellent mirror finish (mirror finish after polishing) and processability is required.
[0006] In order to solve such a technical problem, Patent Document 1 discloses a watch component made of a titanium alloy, which has good processability and can obtain excellent mirror finish.
[0007] Patent Document 2 discloses a high-strength titanium alloy and an eyeglass frame made of the high-strength titanium alloy, wherein the high-strength titanium alloy is characterized in that, in terms of mass%, it contains 0.5 to 5% Zr, 0.5 to 3.5% Fe, 0.05 to 0.5% oxygen, and the remainder is titanium and inevitable components. In addition, Patent Document 2 points out that by containing Zr, Fe, and O in a well-balanced manner, high strength and cold plastic workability can be ensured, and machinability, mirror polishing properties, etc. can be further ensured.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2019 / 044851
[0011] Patent Document 2: Japanese Patent Application Publication No. 2001-220631 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] However, although the techniques of Patent Documents 1 and 2 can ensure certain processability and mirror finish, they may not be able to meet the higher demands in recent years.
[0014] Therefore, the technical problem of the present invention is to provide a titanium alloy plate having excellent workability (particularly bendability) and mirror finish, and glasses including the titanium alloy plate.
[0015] Solutions for solving problems
[0016] The inventors have studied a method for suppressing the generation of concavoconvexity during polishing on the basis of ensuring sufficient workability of titanium alloy plates. As a result, it is found that in addition to improving the strength at medium and high temperatures while refining the grains, it is important to increase the proportion of grains with a prescribed orientation and further reduce the orientation deviation within such grains.
[0017] The present invention has been made in view of the above technical problems. The gist of the present invention is as follows.
[0018] [1] A titanium alloy plate according to one embodiment of the present invention has the following chemical composition, which contains, by mass%, Al: 1.00-7.00%, Fe: 0.10-1.70%, O: 0.05-0.30%, N: 0.000-0.080%, C: 0.000-0.100%, H: 0.000-0.013%, Cu: 0.00-2.00%, Si: 0.00-0.30%, and the remainder: Ti and impurities, and the metallographic structure of the titanium alloy plate contains α phase with an area ratio of 80% or more, the average grain size of the α phase is 20.0 μm or less, and the angle between the c-axis of the α phase and the thickness direction of the titanium alloy plate is within 30 degrees, that is, the α grains. t-30 The area ratio is 20 to 50%, and the α t-30 The area ratio of grains having an average GOS value of 2.0 or less measured by EBSD was 80% or more.
[0019] [2] In the titanium alloy plate described in [1], the angle between the c-axis of the α phase and the width direction of the titanium alloy plate is within 30 degrees, that is, the α phase. c-30 The area ratio can be 8% or more.
[0020] [3] In the titanium alloy plate described in [1], the α t-30 The area ratio may be 20 to 40%.
[0021] [4] In the titanium alloy plate described in [2], the α t-30 The area ratio may be 20 to 40%.
[0022] [5] In the titanium alloy plate described in [1], the chemical composition may include, in mass %, Al: 1.00-3.50%, Fe: 0.10-0.40%, O: 0.05-0.15%, N: 0.000-0.080%, C: 0.000-0.100%, H: 0.000-0.013%, Cu: 0.00-2.00%, Si: 0.00-0.30%, and the remainder: Ti and impurities.
[0023] [6] In the titanium alloy plate described in [2], the chemical composition may include, in mass %, Al: 1.00-3.50%, Fe: 0.10-0.40%, O: 0.05-0.15%, N: 0.000-0.080%, C: 0.000-0.100%, H: 0.000-0.013%, Cu: 0.00-2.00%, Si: 0.00-0.30%, and the remainder: Ti and impurities.
[0024] [7] In the titanium alloy plate described in [3], the chemical composition may include, in mass %, Al: 1.00-3.50%, Fe: 0.10-0.40%, O: 0.05-0.15%, N: 0.000-0.080%, C: 0.000-0.100%, H: 0.000-0.013%, Cu: 0.00-2.00%, Si: 0.00-0.30%, and the remainder: Ti and impurities.
[0025] [8] In the titanium alloy plate described in [4], the chemical composition may include, in mass %, Al: 1.00-3.50%, Fe: 0.10-0.40%, O: 0.05-0.15%, N: 0.000-0.080%, C: 0.000-0.100%, H: 0.000-0.013%, Cu: 0.00-2.00%, Si: 0.00-0.30%, and the remainder: Ti and impurities.
[0026] [9] The titanium alloy plate according to any one of [1] to [8] may have a thickness of 12 mm or less.
[0027]
[10] Another aspect of the present invention relates to glasses comprising the titanium alloy plate according to any one of [1] to [8].
[0028]
[11] Another aspect of the present invention relates to glasses comprising the titanium alloy plate described in [9].
[0029] Effects of the Invention
[0030] According to the above aspect of the present invention, it is possible to provide a titanium alloy plate having excellent workability and mirror finish, and glasses including the titanium alloy plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The diagram shows examples of bending test results, showing an example in which no cracks or irregularities were found (A), an example in which no cracks were found but minute irregularities were found (B), and an example in which cracks were found (C). DETAILED DESCRIPTION
[0032] A titanium alloy plate according to an embodiment of the present invention (titanium alloy plate according to the present embodiment), glasses, and preferred methods for producing the same will be described.
[0033] <Titanium alloy plate>
[0034] The metallographic structure of the titanium alloy plate according to the present embodiment includes 80% or more of the α phase in terms of area ratio, and the average grain size of the α phase is 20.0 μm or less.
[0035] In addition, in the α phase of the titanium alloy plate according to the present embodiment, the angle between the c-axis and the thickness direction of the alloy plate is within 30 degrees, that is, the α phase of the crystal grains. t-30 The area ratio is 20 to 50%, and the α t-30 The area ratio of grains having an average GOS value of 2.0 or less measured by EBSD is 80% or more.
[0036] The following will explain each one separately.
[0037] (Metallurgical Structure)
[0038] [Area ratio of α phase: 80% or more]
[0039] The α phase is the main structure in the metallographic structure of the titanium alloy plate involved in this embodiment. Specifically, the α phase ratio in the entire evaluation surface is 80% or more in terms of area ratio. The area ratio of the α phase is preferably 85% or more, more preferably 90% or more, further preferably 95% or more, and further preferably 98% or more. In addition to the α phase, β phase, Ti2Cu, and Ti5Si3 may also exist. The β phase can contain 1 to 20% because it inhibits grain growth.
[0040] The area ratio of the α phase is determined by the following method.
[0041] Since the α phase is uniformly distributed, the area ratio of each phase constituting the metallographic structure of the titanium alloy plate can be measured on any cross section of the titanium alloy plate. In the present disclosure, for example, it is measured by observing a cross section perpendicular to the plate width direction at a position of 1 / 2 of the plate width of the titanium alloy plate (a position of 1 / 2 of the plate width from the end portion in the plate width direction: the width center).
[0042] Specifically, the cross section perpendicular to the plate width direction at the 1 / 2 position of the titanium alloy plate is polished as an observation surface, and the concentration distribution of Ti, Fe, Cu and Si is measured at a 1.0 μm interval (step length: 1.0 μm) in a 500 μm × 500 μm field of view using SEM (Scanning Electron Microscopy) / EPMA (Electron Probe Microanalyzer). Since Fe, Cu, and Si are enriched in the β phase, Ti2Cu portion, or Ti5Si3 portion, the region where the concentration of these elements is 1.7 times or more of the average value of the entire field of view is set as the β phase, Ti2Cu, or Ti5Si3, and the area ratio of the region relative to the entire field of view is calculated as the area ratio of the β phase, Ti2Cu, or Ti5Si3. In addition, the area ratio of the α phase is calculated by subtracting these area ratios from 100%.
[0043] [Average grain size of α phase: 20.0 μm or less]
[0044] By reducing the average grain size of the main phase α phase, the generation of concavities and convexities during polishing is suppressed and the mirror surface is improved. Specifically, if the average grain diameter of the α phase is less than 20.0 μm, the mirror surface is improved. On the other hand, when the average grain diameter is greater than 20.0 μm, concavities and convexities will be generated due to the grain shape during polishing, and the mirror surface will deteriorate. Therefore, the average grain diameter is less than 20.0 μm. The average grain diameter is preferably less than 15.0 μm.
[0045] The lower limit of the average crystal grain size is not particularly set, but it cannot be made smaller than 2.0 μm in practice, so the average crystal grain size can be set to 2.0 μm or more.
[0046] In the titanium alloy plate according to the present embodiment, the average grain size of the α phase can be measured by observing a cross section perpendicular to the plate width direction of the titanium alloy plate by the following method.
[0047] That is, the cross section of the titanium alloy plate perpendicular to the plate width direction is polished as the observation surface, and the 1.0mm×1.0mm area of the surface is set as the measurement area, and the electron beam is scanned by a scanning electron microscope (SEM), and the electron backscatter diffraction (EBSD) method is used to measure with a step size of 1.0μm to obtain an EBSD pattern. At this time, Titanium (Alpha) and Titanium (Beta) are selected as the measured phases. When the plate thickness is less than 1.0mm, the measurement length can be adjusted so that the measurement area is 1.0mm 2 .
[0048] For the obtained data (EBSD pattern), the average grain size was determined using OIM Analysis software manufactured by TSL Solutions. Specifically, for pixels judged to be Titanium (Alpha), the boundary with an orientation difference of more than 15° was regarded as a grain boundary, and when the area surrounded by the grain boundary contained more than 2 pixels, the area surrounded by the grain boundary was regarded as a grain. The average grain size was obtained by calculating the arithmetic mean of the equivalent circular diameter of the grains in the measured area.
[0049] [In the α phase, the angle between the c-axis and the thickness direction of the titanium alloy plate (plate thickness direction) is within 30 degrees of the grain (α t-30 ) Area ratio: 20% to 50%]
[0050] When titanium alloy plates are used as the blanks for glasses, the surface perpendicular to the plate thickness direction often becomes the polished surface. Since the crystal grains in the α phase with the c-axis approximately parallel to the plate thickness direction (the angle between the c-axis and the plate thickness direction is within 30 degrees) increase the hardness of the polished surface, it helps to improve the mirror finish.
[0051] In order to achieve this effect, the crystal grains (α t-30 ) is set to an area ratio of 20% or more. t-30 The area ratio of α is preferably 25% or more, more preferably 30% or more. t-30 When the area ratio of α increases, the bending property decreases. t-30 The area ratio is less than 50%. t-30 The area ratio is preferably 45% or less, more preferably 40% or less.
[0052] [Preferably, the area ratio of grains in which the angle between the c-axis and the plate width direction of the titanium alloy plate in the α phase is within 30 degrees: 8% or more]
[0053] In the α phase, grains with a crystal orientation in which the c-axis is approximately parallel to the width direction of the titanium alloy plate contribute to the improvement of L-direction bending (bending in which the fold is parallel to the width direction of the plate). Grains (α c-30 ) is 8% or more, a more excellent bendability can be obtained. c-30 The area ratio of α is preferably 8% or more. c-30 The area ratio of α is more preferably 10% or more. c-30 When the area ratio of α is too large, t-30 The area ratio of α is relatively reduced, so c-30 The area ratio can be set to 30% or less.
[0054] The angle between the c-axis and the plate width direction is within 30 degrees. c-30 ) and the area ratio of the grains whose c-axis forms an angle of less than 30 degrees with the plate thickness direction (α t-30 ) can be measured by observing the cross section of the titanium alloy plate perpendicular to the plate width direction.
[0055] Specifically, the cross section of the titanium alloy plate perpendicular to the plate width direction is polished as the observation surface, and the 1.0 mm × 5.0 mm area centered on the center of the plate thickness of the surface is scanned by an electron beam using a scanning electron microscope (SEM), and the EBSD pattern is obtained by measuring the step size of 1.0 μm by the electron backscatter diffraction (EBSD) method. When the plate thickness is less than 1.0 mm, the measurement length can be adjusted so that the measurement area is 5.0 mm. 2 .
[0056] The obtained EBSD data were analyzed using OIM Analysis software manufactured by TSL Solutions (α c-30 ) and (α t-30 At this time, only data with a CI value of 0.1 or more, which indicates orientation reliability, were used for calculation.
[0057] [α t-30 The area ratio of grains with a GOS of 2.0 or less: 80% or more]
[0058] GOS (Grain Orientation Spread) is a parameter that indicates the orientation deviation within a grain and can be obtained for each grain. The smaller this parameter is, the smaller the orientation deviation is.
[0059] α t-30 In the case of grains where the angle between the c-axis and the plate thickness direction is within 30 degrees, the deviation within the grains is further reduced, thereby achieving uniform polishing during polishing and improving the mirror surface. Specifically, if the area ratio of grains with a GOS of less than 2.0 is 80% or more, the mirror surface is improved. t-30 When the area ratio of grains having a GOS of 2.0 or less is less than 80%, the surface roughness after polishing becomes non-uniform, and the mirror surface property deteriorates.
[0060] α t-30 The area ratio of grains with a GOS of 2.0 or less is preferably 85% or more, more preferably 90% or more. The upper limit of the area ratio of grains with a GOS of 2.0 or less is not limited and may be 100%, or may be 99% or less in consideration of manufacturing load, etc.
[0061] α t-30The area ratio of grains having a GOS of 2.0 or less can be determined by the following method.
[0062] The cross section of the titanium alloy plate perpendicular to the plate width direction was polished as the observation surface, and the 1.0 mm × 5.0 mm area of the surface was scanned by an electron beam using a scanning electron microscope (SEM), and the EBSD pattern was obtained by measuring the EBSD pattern with a step size of 1.0 μm. When the plate thickness is less than 1.0 mm, the measurement length can be adjusted so that the measurement area is 5.0 mm. 2 .
[0063] The obtained EBSD data can be used to evaluate the area ratio of grains having a GOS of 2.0 or less using OIM Analysis software manufactured by TSL Solutions.
[0064] Specifically, the boundary with an orientation difference of 15° or more is regarded as a grain boundary, and when the area surrounded by the grain boundary contains two or more pixels, the area surrounded by the grain boundary is regarded as a grain. Then, the α t-30 The GOS of each grain is calculated to find the area ratio where this value is 2.0 or less.
[0065] (Chemical Composition)
[0066] The chemical composition of the titanium alloy plate according to the present embodiment is in the following range. Hereinafter, % in relation to the content of an element means mass % unless otherwise specified.
[0067] [Al: 1.00~7.00%]
[0068] Al is an element that stabilizes the α phase. In addition, Al is an element that increases the hardness of titanium alloy plates at room temperature and in the medium and high temperature range. The polishing of ornaments is mostly carried out in a dry manner, and the decrease in hardness caused by processing heat often leads to deterioration of mirror properties. Therefore, by containing Al, which has an effect not only on the increase of hardness at room temperature but also in the medium and high temperature range, the mirror properties are improved. In order to obtain the improvement effect of the mirror properties, the Al content is set to 1.00% or more. The Al content is preferably 1.50% or more.
[0069] On the other hand, when the Al content is too high, ductility decreases and bending formability deteriorates. Therefore, from the perspective of formability, the Al content is set to 7.00% or less. The Al content is preferably 3.50% or less, more preferably 3.00% or less, and even more preferably 2.50% or less.
[0070] [Fe: 0.10~1.70%]
[0071] Fe is an element that stabilizes the β phase. By containing Fe, the β phase is formed during annealing. The β phase helps to suppress the grain growth of the α phase grains through the pinning effect, so by containing Fe, the grains can be refined. In order to obtain this effect, the Fe content is set to 0.10% or more. The Fe content is preferably 0.15% or more.
[0072] On the other hand, when the Fe content is too high, the formability of the titanium alloy sheet deteriorates. Therefore, from the viewpoint of formability, the Fe content is set to 1.70% or less. The Fe content is preferably 0.40% or less, and more preferably 0.30% or less.
[0073] [O: 0.05~0.30%]
[0074] O is an element that increases the hardness of the titanium alloy plate and improves the mirror finish. To achieve this effect, the O content is set to 0.05% or more. The O content is preferably 0.07% or more.
[0075] On the other hand, when the O content is too high, the ductility of the titanium alloy plate decreases and the bending formability deteriorates. Therefore, from the perspective of formability, the O content is set to 0.30% or less. The O content is preferably 0.20% or less, more preferably 0.15% or less, and further preferably 0.12% or less.
[0076] [N: 0.000~0.080%]
[0077] N is an element that affects the strength and workability of titanium alloy plates. When the N content is too much, the ductility of the titanium alloy plate decreases and the bending formability deteriorates. Therefore, the N content is set to 0.080% or less. The N content is preferably 0.060% or less, more preferably 0.040% or less, and further preferably 0.020% or less.
[0078] N is not necessarily contained, and the N content may be 0.000%. However, it is industrially difficult to make the N content less than 0.001%. Therefore, the N content may be 0.0001% or more, or 0.002% or more, or 0.003% or more.
[0079] [C: 0.000~0.100%]
[0080] C has a smaller influence on strength and workability than O and N, but is an element that affects strength and workability like O and N. When the C content is too high, workability decreases, so the C content is set to 0.100% or less. The C content is preferably 0.080% or less, more preferably 0.060% or less, further preferably 0.040% or less, and further preferably 0.020% or less.
[0081] In the titanium alloy plate according to the present embodiment, the inclusion of C is not essential, and the C content may be 0.000%. However, it is industrially difficult to reduce the C content to less than 0.001%, so the C content may be 0.001% or more, or 0.002% or more, or 0.003% or more.
[0082] [H: 0.000~0.013%]
[0083] H is an element that causes embrittlement, but generally, if the content is 0.013% or less, although there is a concern about embrittlement, it can be used without problems in practical applications. Therefore, the H content is set to 0.013% or less. The H content is preferably 0.010% or less, more preferably 0.008% or less, and further preferably 0.006% or less, 0.004% or less, or 0.003% or less.
[0084] The inclusion of H is not essential, and the H content may be 0.000%, but may be 0.001% or more, 0.002% or more, or 0.003% or more as necessary.
[0085] [Cu: 0.00~2.00%]
[0086] Cu is an element that increases the strength in the room temperature to medium temperature range. Therefore, it may be contained. In order to obtain the above-mentioned effect, it is preferable to set the Cu content to 0.50% or more.
[0087] On the other hand, when the Cu content exceeds 2.00%, Ti2Cu precipitates excessively and ductility deteriorates. Therefore, the Cu content is set to 2.00% or less.
[0088] [Si: 0.00~0.30%]
[0089] Si is an element that increases the strength in the room temperature to medium temperature range. Therefore, Si may be contained. In order to obtain the above-mentioned effect, the Si content is preferably set to 0.10% or more.
[0090] On the other hand, when the Si content exceeds 0.30%, Ti5Si3 precipitates excessively and ductility deteriorates. Therefore, the Si content is set to 0.30% or less. The Si content is preferably 0.20% or less, more preferably 0.18% or less, and further preferably 0.15% or less.
[0091] [Ballast: Ti and impurities]
[0092] The chemical composition of the titanium alloy plate according to the present embodiment contains the above, and the balance is Ti and impurities.
[0093] As impurities, there are, for example, metal elements from waste materials used as raw materials. Specifically, when promoting the use of waste materials as raw materials, in addition to the above-mentioned elements (Al, Fe, O, N, C, H, Cu, Si), metal elements other than these elements are also mixed in. Although the mixing of these elements can be prevented by strict management, the processing cost is high. Therefore, in the titanium alloy plate involved in the present embodiment, in order to provide a cheap titanium alloy plate, the mixing of metal elements from waste materials (containing as impurities) is allowed within the range that does not hinder the effect of the titanium alloy plate involved in the present embodiment. As metal elements from waste materials, Cr, Ni, Mo, V, Sn, Co, Zr, Nb, Mn, Ta, W, Hf, Pd, Ru can be listed. In the case of containing these elements, there is no problem as long as their content is, for example, less than 0.10% respectively and the total amount is less than 0.50%.
[0094] (plate thickness)
[0095] The thickness of the titanium alloy plate according to the present embodiment is not limited, but considering that it is used as a raw material for glasses, the thickness is preferably 12.0 mm or less. In addition, from the perspective of ensuring rigidity, the thickness is preferably 0.2 mm or more.
[0096] <Glasses>
[0097] The glasses according to the present embodiment use a titanium alloy obtained by cold working the titanium alloy plate according to the present embodiment to manufacture the frame portion, etc. Therefore, at least a portion of the glasses according to the present embodiment includes the titanium alloy plate according to the present embodiment.
[0098] <Method for producing titanium alloy plate>
[0099] The titanium alloy plate according to the present embodiment can achieve its effects regardless of the manufacturing method as long as it has the above-mentioned characteristics. However, a manufacturing method including the following steps (I) to (IV) is preferred because it can be stably manufactured.
[0100] (I) A melting step is to melt a titanium raw material produced to a predetermined purity by a known method to produce a predetermined ingot.
[0101] (II) A slab forming step of processing the ingot as required to obtain a slab.
[0102] (III) A hot rolling step of hot rolling the ingot or the slab to obtain a titanium alloy plate.
[0103] (IV) A hot rolled sheet annealing step of annealing the titanium alloy sheet after the hot rolling step.
[0104] In addition, after obtaining α t-30In the case of a titanium alloy plate in which the area ratio of the titanium alloy is further improved, it is preferable to include the following production methods (I) to (VI).
[0105] (I) A melting step is to melt a titanium raw material produced to a predetermined purity by a known method to produce a predetermined ingot.
[0106] (II) A slab forming step of processing the ingot to obtain a slab.
[0107] (III) A hot rolling step of hot rolling the ingot or the slab to obtain a titanium alloy plate.
[0108] (IV′) A hot rolled sheet annealing step is performed as necessary to anneal the titanium alloy sheet after the hot rolling step.
[0109] (V) a cold rolling step of cold rolling the titanium alloy sheet after the hot rolling step or the hot rolled sheet annealing step.
[0110] (VI) an annealing step of annealing the titanium alloy sheet after the cold rolling step.
[0111] In addition, the method for producing a titanium alloy plate according to the present embodiment may include the following steps after the hot-rolled plate annealing step or after the annealing step, as necessary.
[0112] (VII) Surface temper rolling / stretching correction step, wherein the titanium alloy plate is subjected to surface temper rolling or stretching correction.
[0113] Hereinafter, each step will be described.
[0114] For steps and conditions not described in detail, known conditions can be used.
[0115] (I) Melting process
[0116] In the melting process, a titanium raw material manufactured to a specified purity is melted by a known method, and other elements are added as needed to form an ingot having a specified chemical composition (in the case of obtaining a titanium alloy plate involved in the present embodiment, the same chemical composition as the titanium alloy plate involved in the present embodiment). The melting method is not limited, but for example, a vacuum arc melting method (VAR method) or an electron beam melting method (EB method) can be used.
[0117] (II) Opening process
[0118] In the process of opening the blank, the obtained ingot is processed into a slab by known initial rolling or forging. The slab (titanium slab) obtained through the above-mentioned opening process can be cut, cleaned, etc. by known methods as needed. This step can be omitted as needed. The titanium slab can also be pre-treated by cleaning, cutting, etc. as needed.
[0119] (III) Hot rolling process
[0120] In the hot rolling process, the ingot obtained in the melting process or the slab obtained in the blooming process is heated and hot rolled to produce a titanium alloy plate.
[0121] When obtaining the titanium alloy plate according to the present embodiment, it is important to control the heating temperature, the finishing temperature (hot rolling finishing temperature), and the reduction ratio during hot rolling.
[0122] Heating temperature: T β80 Below ℃
[0123] In order to develop a crystal orientation with an angle of less than 30 degrees between the c-axis and the thickness direction, it is necessary to process in a temperature range with more α phase. Therefore, the heating temperature during hot rolling is set to the temperature at which the volume fraction of β phase reaches 80% (T β80 )(℃) or less. Heating temperature is greater than T β80 ℃, the concentration of crystal orientations with an angle of less than 30 degrees between the c-axis and the plate thickness direction decreases. In addition, even if grains with an angle of less than 30 degrees between the c-axis and the plate thickness direction are formed during hot rolling, sufficient strain cannot be imparted, and recrystallization may not be possible even after subsequent annealing. In this case, the proportion of grains with large GOS increases, and the mirror finish deteriorates.
[0124] On the other hand, in order to develop a crystal orientation with an angle of less than 30 degrees between the c-axis and the plate width direction, which is excellent in L-bendability, it is necessary to roll in the β phase. c-30 In the case of an area ratio of , the heating temperature is preferably set to a temperature at which the β phase ratio reaches 20% (T β20 )(℃) or above.
[0125] From the perspective of reducing deformation resistance and controlling texture, hot rolling of conventional titanium alloys is usually carried out under heating in the β single phase region. However, in the present embodiment, based on new insights (when rolling is carried out under heating in the β single phase region, the intragranular orientation dispersion of the grains after transformation into the α phase is large, and the proportion of grains in which the angle between the c-axis and the thickness direction in the texture is within 30 degrees is also low, resulting in deterioration of polishability), hot rolling is carried out under the above conditions.
[0126] Hot rolling end temperature: 600℃ or above and T β10 Below ℃
[0127] The normal line height of the bottom surface (0001) α of the α phase is concentrated in the plate width direction (T direction) perpendicular to the rolling direction and the plate surface normal line direction, which is called T-texture. Although it is an orientation with excellent bending in the L direction, the T-texture grains will immediately become large GOS grains after the transformation from β phase to α phase. In order to improve this, it is necessary to perform annealing under specified conditions after applying strain to make it recrystallized.
[0128] If the volume fraction of the β phase is high at the end of hot rolling, the proportion of T-texture grains with large GOS increases, and the mirror finish deteriorates. Specifically, if the hot rolling end temperature is higher than the temperature at which the volume fraction of the β phase reaches 10% (T β10 Therefore, the hot rolling end temperature is set to T β10 below ℃.
[0129] On the other hand, when the hot rolling end temperature is less than 600℃, it may cause α t-30 The area ratio of the titanium alloy plate becomes too high or cracks are generated during rolling, so it is set to be above 600°C. Here, cracks include so-called end cracks and internal cracks. If internal cracks occur, it is difficult to carry out subsequent processes. On the other hand, if end cracks occur, the possibility of plate breakage becomes high, especially in the case of continuous rolling in which tension is applied to the titanium alloy plate while rolling.
[0130] The above T β10 , T β20 , T β80 , the following T β30 , T β50 The temperature at which the β phase reaches a specified volume ratio can be obtained from the phase diagram. The phase diagram can be obtained by, for example, the CALPHAD (Computer Coupling of Phase Diagrams and Thermochemistry) method, for example, Thermo-Calc Software AB's comprehensive thermodynamic calculation system, i.e., Thermo-Calc, and a specified database (TI3) can be used for this purpose. At this time, since Ti2Cu and Ti5Si3 do not affect the change in texture, the calculation is performed using only the hcp structure and the bcc structure.
[0131] Total reduction rate: more than 80%
[0132] When the total reduction ratio of hot rolling ((plate thickness before rolling - plate thickness after rolling) / plate thickness before rolling × 100) is less than 80%, the concentration of crystal orientation within 30 degrees between the c-axis and the plate thickness direction decreases. Therefore, the total reduction ratio of hot rolling is set to 80% or more.
[0133] (IV) or (IV') Hot rolled sheet annealing process
[0134] In the hot rolled sheet annealing step, the titanium alloy sheet after the hot rolling step is annealed. By performing annealing under predetermined conditions, the orientation deviation within the grains can be reduced (the proportion of grains with a small GOS can be increased).
[0135] Specifically, when the annealing temperature is 600°C or higher and T β50 Annealing is performed under the conditions of a combination of temperature and time of 0.1°C or less and satisfying the following formula (1).
[0136] 21500≤(T+273)×(Log(t)+20)≤25000 Formula (1)
[0137] Wherein, (T+273)×(Log(t)+20) is a function called Larson-Miller parameter (P), T is the annealing temperature (° C.), t is the annealing time (s), and Log represents the common logarithm.
[0138] When the annealing temperature is lower than 600° C., recrystallization may not be completed, GOS may become larger, and the mirror property may be deteriorated. Therefore, the annealing temperature is set to 600° C. or higher. The annealing temperature is preferably 630° C. or higher.
[0139] On the other hand, the annealing temperature is higher than T β50 ℃, the volume fraction of the β phase may become too high during annealing, and the concentration of the area fraction of the grains whose c-axis and thickness direction form an angle of less than 30 degrees will decrease. Therefore, the annealing temperature is set to T β50 ℃ or less. The annealing temperature is preferably T β30 below ℃.
[0140] In addition, when P (Larson-Miller parameter) is less than 21500, recrystallization may not be completed, GOS may become large, and the mirror surface may deteriorate. Therefore, P is 21500 or more. P is preferably 23000 or more.
[0141] On the other hand, when P exceeds 25000, the average crystal grain size may exceed 20.0 μm, and the mirror surface property may be deteriorated. Therefore, P is 25000 or less. P is preferably 24500 or less, and more preferably 24000 or less.
[0142] However, if the cold rolling step and the annealing step are performed under the conditions described later, this step can be omitted.
[0143] (V) Cold rolling process
[0144] The titanium alloy plate involved in this embodiment can be obtained by annealing the hot rolled plate. Among them, by cold rolling and annealing under specified conditions, the αt-30 Therefore, as needed, the titanium alloy sheet after the hot rolling step or after the hot rolled sheet annealing step is cold rolled.
[0145] When cold rolling is performed, cold rolling may be performed once (a series without intermediate annealing), or two or more cold rollings may be performed with one or more intermediate annealing interposed therebetween.
[0146] In the case of cold rolling, the reduction rate of one time (before the initial intermediate annealing, between the intermediate annealing, and after the final intermediate annealing) is preferably set to 60% or less. When the reduction rate is greater than 60%, cracks may occur inside, resulting in deterioration of workability, or cracks may appear on the surface depending on the processing method, resulting in deterioration of polishability. In addition, when increasing α c-30 In the case of an area ratio of α, the reduction rate of one time is preferably 60% or less. More preferably, it is 50% or less. In addition, since cold rolling is not necessary, the reduction rate can be 0%, but in increasing α t-30 In the case of an area ratio of , it is preferred that the reduction rate be 30% or more.
[0147] Cold rolling and intermediate annealing may be repeated several times, but from the viewpoint of productivity, the number of cold rolling times is preferably 4 times or less.
[0148] (VI) Annealing process
[0149] In the annealing step, the titanium alloy sheet after the cold rolling step is annealed. When annealing is performed, the conditions are the same as those in the hot rolled sheet annealing step (IV).
[0150] That is, when the annealing temperature is 600°C or higher and T β50 Annealing is performed under the conditions of a combination of temperature and time of 0.1°C or less and satisfying the following formula (1).
[0151] 21500≤(T+273)×(Log(t)+20)≤25000 Formula (1)
[0152] (VII) Surface tempering / stretching correction process
[0153] In the temper rolling / stretching step, after the hot rolled sheet annealing step or after the annealing step in the case where the cold rolling step and the annealing step are performed, the titanium alloy sheet is temper rolled or stretched to adjust the shape.
[0154] <How to make glasses>
[0155] The glasses involved in this embodiment can be manufactured by processing the titanium alloy plate involved in this embodiment into a predetermined shape by a known method such as cold working to form a glasses component, and combining the glasses component with a lens or the like. t-30 Since the area ratio of may change, it is preferred not to perform processing accompanied by heat treatment during processing.
[0156] Example
[0157] The titanium ingots as the blanks of the titanium alloy plates shown in Table 1 were manufactured by vacuum arc melting (VAR). Then, by initial rolling or forging, slabs with a thickness of 60 mm × a width of 120 mm × a length of 250 mm were manufactured. In Table 1, the remainder is Ti and impurities. Although the content of impurity elements is omitted, they are 0.10 mass % or less respectively and 0.50 mass % or less in total.
[0158] The method for measuring the chemical composition of the slab is as follows.
[0159] The contents of O and N were measured by thermal conductivity-infrared absorption using an oxygen-nitrogen simultaneous analyzer. The content of C was measured by infrared absorption using a carbon-sulfur analyzer. H was measured by thermal conductivity using a hydrogen analyzer. The contents of other elements were measured by ICP emission spectrometry using a sequential ICP emission spectrometer.
[0160] In addition, for the titanium billets A to AC shown in Table 1, the phase diagram of the titanium alloy was obtained by the CALPHAD method using Thermo-Calc, a comprehensive thermodynamic calculation system of Thermo-Calc Software AB, and a specified database (TI3), and the temperatures T at which the volume fraction of the β phase reaches 10%, 20%, 30%, 50%, and 80% were calculated. β10 , T β20 , T β30 , T β50 , T β80 .
[0161] The obtained slabs were hot rolled, annealed, cold rolled, and annealed under the conditions shown in Tables 2-1 and 2-2 to obtain titanium alloy plates having the plate thicknesses shown in Table 3. If the process was not performed, it is indicated as "-" in the table.
[0162] Regarding cold rolling, invention examples 3, 6, and 7 were subjected to 2 to 5 cold rolling cycles with intermediate annealing. The first rolling reduction ratio in the table indicates the cold rolling reduction ratio with the largest rolling reduction ratio among the multiple cold rolling cycles.
[0163] Among them, only in Comparative Example 22, the hot-rolled sheet was not cold-rolled after annealing, but was heated to 850° C. and hot forged with a cross-sectional reduction rate of 30%, and then annealed at 800° C. for 120 seconds.
[0164] Although not shown in the table, the chemical composition of each manufactured hot-rolled plate is the same as the chemical composition of the titanium slab shown in Table 1.
[0165] The area ratio of the α phase, the average grain size of the α phase, and the α t-30 The area ratio, α c-30 The area ratio, α t-30 The area ratio of the grains having an average value of GOS measured by EBSD of 2.0 or less.
[0166] When measuring EBSD, the acceleration voltage during measurement was set to 15 kV, the irradiation current was set to about 40 nA, and the magnification was set to 100. The version of OIM Analysis used was 7.31.
[0167] The results are shown in Table 3.
[0168] In the metallographic structure, in addition to the α phase there are β phase, Ti2Cu and / or Ti5Si3.
[0169] The workability and mirror finish of the obtained titanium alloy plate were determined by the following method.
[0170] <Mirror surface>
[0171] A 10 mm × 10 mm sample was cut from a titanium alloy plate and embedded in epoxy resin to make the plate surface a polished surface. Then, wet polishing was performed in the order of coarse to fine sandpaper, and dry polishing was used for fine polishing to obtain a mirror surface.
[0172] After dry polishing, the mirror surface is evaluated. In the mirror surface evaluation, the parameter representing the image clarity, DOI (Distinctness of Image), is used. The DOI is measured according to ASTM D 5767 (2018) at an incident light angle of 20°. DOI can be measured, for example, by an appearance analyzer Rhopoint IQ Flex20 manufactured by Rhopoint Instruments.
[0173] The higher the DOI, the better the mirror surface. In the present invention, a DOI of 60 or more can be judged as excellent in mirror surface.
[0174] <Processability (bendability)>
[0175] Nine bending test pieces with a width of 25 mm and a length of 50 mm were cut out from the titanium alloy plate. Then, a 90° bending test was performed in the 50 mm length direction, and the peripheral surface after 90° bending was observed with a stereo microscope. At this time, the curvature radius R of the inner side of the bending test was set to three types according to the plate thickness: R = 1.25 × plate thickness (mm), R = 1.50 × plate thickness (mm), and R = 1.75 × plate thickness (mm).
[0176] The evaluation index was set as follows. If no cracks were observed on the outer peripheral surface after 90° bending (evaluation of A, B, C, or D) at 1.75×plate thickness (mm), the workability was judged to be excellent.
[0177] The bending test is performed in the order of the radius of curvature from small to large. If no crack occurs, the test is terminated. The bending test is performed 3 times for each radius of curvature. That is, the bending test is performed on 3 test pieces with R = 1.25 × plate thickness. If no crack is found in all test pieces, the evaluation is A, and the test is terminated.
[0178] On the other hand, if cracks are found in one or more of the three test pieces in the bending test set at R = 1.25 × plate thickness, the other three test pieces are subjected to a bending test set at R = 1.50 × plate thickness. As a result, if no cracks or irregularities are found on the peripheral surface, the evaluation is B, and if no cracks are found but minute irregularities are found, the evaluation is C, and the test is terminated.
[0179] On the other hand, if cracks are found in one or more of the three specimens in the bending test at R = 1.50 × plate thickness, the other three specimens are subjected to a bending test at R = 1.75 × plate thickness. As a result, if no cracks are found on the peripheral surface, the evaluation is D, and if cracks are found, the evaluation is F.
[0180] (Evaluation Index)
[0181] A: No cracks or irregularities were observed on the outer peripheral surface after bending at 90° with R=1.25×plate thickness (mm).
[0182] B: No cracks or irregularities were observed on the outer peripheral surface after bending at 90° with R=1.50×plate thickness (mm).
[0183] C: There are no cracks on the outer peripheral surface after bending at 90° with R=1.50×plate thickness (mm), but minute irregularities are observed.
[0184] D: No cracks were observed on the outer peripheral surface after bending at 90° with R=1.75×plate thickness (mm).
[0185] F: Cracks were observed on the outer peripheral surface after 90° bending at R=1.75×plate thickness (mm).
[0186] Figure 1 An example of the outer peripheral surface after the bending test is shown.
[0187] [Table 1]
[0188]
[0189] [Table 2-1]
[0190]
[0191] [Table 2-2]
[0192]
[0193] [Table 3]
[0194]
[0195] From Tables 1 to 3, it can be seen that the area ratio of the α phase, the average grain size of the α phase, and the t-30 The area ratio and α t-30 In Invention Examples 1 to 33, in which the average value of GOS measured by EBSD was 2.0 or less and the area ratio of grains was within the range of the present invention, excellent bendability and mirror surface properties were obtained.
[0196] On the other hand, in terms of chemical composition, area ratio of α phase, average grain size of α phase, α t-30 The area ratio, α t-30 In Comparative Examples 1, 2, 4 to 22, in which one or more of the area ratios of grains having an average GOS value of 2.0 or less measured by EBSD was outside the scope of the present invention, sufficient bendability or sufficient mirror finish could not be obtained. Comparative Example 3 could not be evaluated because cracks occurred in the hot-rolled sheet and subsequent processes were not performed.
[0197] In Comparative Example 1, the heating temperature during hot rolling was high, resulting in t-30 The area ratio of the crystal grains with an average GOS value of less than 2.0 is beyond the scope of the present invention. As a result, the mirror surface is poor.
[0198] In Comparative Example 2, the hot rolling end temperature was high, resulting in α t-30 The area ratio of the crystal grains with an average GOS value of less than 2.0 is beyond the scope of the present invention. As a result, the mirror surface is poor.
[0199] In Comparative Example 3, the rolling end temperature was low, which caused end cracks in the hot-rolled sheet. Therefore, the production was stopped midway and no evaluation was performed.
[0200] In Comparative Example 4, the hot rolling end temperature was low, resulting in αt-30 The area ratio of exceeds the scope of the present invention. As a result, the bendability is poor. In Comparative Example 4, due to the rolling at low temperature, end cracks were generated, but hot rolling was performed by reversible rolling, and then the subsequent process was performed.
[0201] In Comparative Example 5, the hot rolling reduction ratio was low, resulting in α t-30 The area ratio of is beyond the scope of the present invention. As a result, the mirror surface is poor.
[0202] In Comparative Example 6, the holding temperature during hot-rolled sheet annealing was low and the Larsen-Miller parameter was small, so the area ratio of grains having an average GOS value of 2.0 or less was outside the range of the present invention. As a result, the mirror surface was poor.
[0203] In Comparative Example 7, due to the high holding temperature during hot-rolled sheet annealing, the Larsen-Miller parameter is large, resulting in α t-30 The area ratio of is beyond the scope of the present invention. As a result, the mirror surface is poor.
[0204] In Comparative Example 8, the Larsen-Miller parameter during hot-rolled sheet annealing was large, resulting in an average grain size of the α phase exceeding the range of the present invention. As a result, the mirror surface property was poor.
[0205] In Comparative Example 9, since the Larsen-Miller parameter during hot-rolled sheet annealing was small, the area ratio of grains having an average GOS value of 2.0 or less was outside the range of the present invention. As a result, the mirror surface property was poor.
[0206] In Comparative Example 10, the Al content was small. As a result, the mirror surface property was poor.
[0207] In Comparative Example 11, the Al content was high. As a result, the bendability was poor.
[0208] In Comparative Example 12, the Fe content was small and the average grain size of the α phase was out of the range of the present invention. As a result, the mirror surface property was poor.
[0209] In Comparative Example 13, the Fe content was high and the area ratio of the α phase was small. As a result, the bendability was poor.
[0210] In Comparative Example 14, the O content was small. As a result, the mirror surface property was poor.
[0211] In Comparative Example 15, the O content was high. As a result, the bendability was poor.
[0212] In Comparative Example 16, the C content was large. As a result, the bendability was poor.
[0213] In Comparative Example 17, the N content was high. As a result, the bendability was poor.
[0214] In Comparative Example 18, the H content was high. As a result, the bendability was poor.
[0215] In Comparative Example 19, the Cu content was high. As a result, the bendability was poor.
[0216] In Comparative Example 20, the Si content was high. As a result, the bendability was poor.
[0217] In Comparative Example 21, since the heating temperature during hot rolling and the hot rolling end temperature were high, the average grain size of the α phase, the area ratio of the grains with an average GOS value of 2.0 or less, and the α t-30 The area ratio of is beyond the scope of the present invention. As a result, the mirror surface is poor.
[0218] In Comparative Example 22, forging was performed under the conditions in the table, α t-30 The area ratio of is beyond the scope of the present invention. As a result, the mirror surface is poor.
[0219] Industrial Applicability
[0220] According to the present invention, it is possible to provide a titanium alloy plate having excellent workability and mirror finish, and glasses including the titanium alloy plate.
Claims
1. A titanium alloy plate, characterized in that: It has the following chemical composition, Included by quality Al:1.00~7.00%、 Fe: 0.10~1.70%, O:0.05~0.30%、 N:0.000~0.080%、 C:0.000~0.100%、 H:0.000~0.013%、 Cu: 0.00~2.00%, Si: 0.00~0.30%, Balance: Ti and impurities, The metallographic structure of the titanium alloy plate includes 80% or more of the α phase in terms of area ratio. The average grain size of the α phase is 20.0 μm or less, In the α phase, the angle between the c-axis and the thickness direction of the titanium alloy plate is within 30 degrees, that is, the α t-30 The area ratio is 20-50%. The α t-30 The area ratio of grains having an average GOS value of 2.0 or less measured by EBSD is 80% or more.
2. The titanium alloy plate according to claim 1, characterized in that: In the α phase, the angle between the c-axis and the width direction of the titanium alloy plate is within 30 degrees, that is, the α c-30 The area rate is more than 8%.
3. The titanium alloy plate according to claim 1, characterized in that: The α t-30 The area ratio is 20 to 40%.
4. The titanium alloy plate according to claim 2, characterized in that: The α t-30 The area ratio is 20 to 40%.
5. The titanium alloy plate according to claim 1, characterized in that: The chemical composition includes by mass % Al:1.00~3.50%、 Fe: 0.10-0.40%, O:0.05~0.15%、 N:0.000~0.080%、 C:0.000~0.100%、 H:0.000~0.013%、 Cu: 0.00~2.00%, Si: 0.00~0.30%, Balance: Ti and impurities.
6. The titanium alloy plate according to claim 2, characterized in that: The chemical composition includes, by mass%, 1.00 to 3.50% Al, Fe: 0.10~0.40%, O:0.05~0.15%、 N:0.000~0.080%、 C:0.000~0.100%、 H:0.000~0.013%、 Cu: 0.00~2.00%, Si: 0.00~0.30%, Balance: Ti and impurities.
7. The titanium alloy plate according to claim 3, characterized in that: The chemical composition includes, by mass%, 1.00 to 3.50% Al, Fe: 0.10~0.40%, O:0.05~0.15%、 N:0.000~0.080%、 C:0.000~0.100%、 H:0.000~0.013%、 Cu: 0.00~2.00%, Si: 0.00~0.30%, Balance: Ti and impurities.
8. The titanium alloy plate according to claim 4, characterized in that: The chemical composition includes by mass % Al:1.00~3.50%、 Fe: 0.10~0.40%, O:0.05~0.15%、 N:0.000~0.080%、 C:0.000~0.100%、 H:0.000~0.013%、 Cu: 0.00~2.00%, Si: 0.00~0.30%, Balance: Ti and impurities.
9. The titanium alloy plate according to any one of claims 1 to 8, characterized in that The plate thickness is less than 12mm. 10 . Eyeglasses comprising the titanium alloy plate according to claim 1 .
11. Eyeglasses comprising the titanium alloy plate according to claim 9.
Citation Information
Patent Citations
High-strength titanium alloy
JP2001220631A
Planar lighting device
JP2022136623A
Clock component
WO2019044851A1